JAPAN AS AN ECONOMIC MODEL: IS IT STILL RELEVANT? - Ronald Nangoi (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2018)
Japan’s dominant position in world economy has currently been replaced by China. Yet, Indonesia which has close relationship with Japan could still learn from this country in its economic and business development. The study perceived from both macro-economic and micro-business perspectives is to affirm that it’s still relevant for Japan to be an economic model due to its past contribution to the rise of Asian and world economy and its long experience in manufacturing and management, its reliance on quality and productivity, and its business ethics as well. Key words: Asian and world economy, competitive manufacturing, management system, cultural values, JIEPA Abstrak Dewasa ini posisi dominan Jepang pada ekonomi dunia telah digeser oleh Tiongkok. Namun, Indonesia yang memiliki hubungan erat dengan Jepang sebenarnya masih bisa belajar dari negara dalam pembangunan ekonomi dan bisnis. Studi yang ditinjau dari sudut pandang makro-ekonomi dan mikro-bisnis dimaksudkan untuk mempertegas bahwa masih relevan bagi Jepang untuk menjadi model ekonomi sehubungan dengan sumbangsih Jepang di masa lalu bagi bangkitnya ekonomi Asia dan dunia serta pengalaman Jepang dalam manufakturing dan manajemen, pengandalan Jepang atas mutu dan produktivitas, dan juga etika bisnis. Kata kunci: ekonomi Asia dan dunia, manufakturing yang berdaya saing, sistem manajemen, nilai-nilai budaya, JIEPA